Anaplastic Transformation in Myxopapillary Ependymoma: A Report of 2 Cases and Review of the Literature. Issue 10 (2nd August 2020) - Gitto, Lorenzo; Serinelli, Serenella; Galbraith, Kristyn; Williams, Michael; Mirchia, Kanish; Galgano, Michael A; Krishnamurthy, Satish; de la Roza, Gustavo; Viapiano, Mariano S; Walker, Jamie M; Jour, George; Serrano, Jonathan; et al.
Abstract: Myxopapillary ependymoma (MPE) is a relatively common neoplasm arising primarily in the filum terminale/lumbosacral region of the spinal cord. It is designated as a grade I tumor in the most recent WHO Classification of Tumours of the CNS, although aggressive clinical behavior can be observed, especially in cases arising in an extradural location. Anaplastic transformation in MPE is exceedingly rare with <20 examples reported in the English literature, and consensus on diagnostic features and definitive grading remain to be determined. Here, we present 2 cases of recurrent MPE with anaplastic features, both of which had histology consistent with conventional MPE as well as areas with significant atypia, frequent mitotic figures, elevated Ki-67 proliferation indices (>10%–50%), necrosis, and focal vascular proliferation. Targeted next-generation sequencing panels revealed no definitive pathogenic mutations or fusion proteins in either case. Copy number profiling, methylation profiling, and t-Distributed Stochastic Neighbor Embedding were performed to investigate the molecular characteristics of these tumors. To the best of our knowledge, these are the first reported cases of MPE with anaplastic features with methylation profiling data. In addition, we review the literature and discuss common histologic and molecular findings associated with anaplastic features in MPE.